Understanding the appropriate teaching aid product design used for 'special recovery classes' to enhanced student's reading skill / Muhammad Syazwan Mohamad Sharil - Mohamad Sharil, Muhammad Syazwan (2022)
Student face problem in learning must sign up for special recovery classes in primary school. The primary school particular in recovery class, has difficulty reading, writing, and calculation. Base on Utusan Malaysia at 19th March 2019, Dr. Mahathir Mohamad say 'Marilah jadikan sekolah kebangsaan hebat semula'. From these slogans, every primary school must upgrade their learning system to solve the students' problems in studies. Research focused on students have difficulty in reading and signed up for special recovery classes. Research objective focus to analyse teachers' tools to help primary students with poor reading skills and to propose how teaching aids work on students in special recovery classes with poor reading skills. Mixed method chosen as a research method for data collection to achieve aim and research objective. Through interviews and questionnaires from respective respondents, among teachers and parent to answer the research objective. After doing the analysis from data collected, researcher state criteria of product design teaching aids guideline for stakeholder in order develop their teaching aids to ensure the poor reading skill student will overcome and benefit the educational learning system. Thus, the knowledge gained from the research study will help Malaysian design industry.